The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1039/d2ta01325h
|View full text |Cite
|
Sign up to set email alerts
|

A cobalt covalent organic framework: a dual-functional atomic-level catalyst for visible-light-driven C–H annulation of amides with alkynes

Abstract: The merger of transition-metal catalysis and photoredox catalysis enables a balance between the elegant chemical transformation and the rational use of light energy. Previously, it was always accomplished with the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 78 publications
0
21
0
Order By: Relevance
“…Then, they were used as heterogeneous photocatalysts in sequence for the visible-light-induced three-component reaction of quinoxalin-2(1 H )-one ( 1a ), phenyl propylene ( 2a ), and CF 3 SO 2 Na under the blue LED irradiation in dioxane at room temperature for 24 h. We observed that most of them were effective for the reaction, delivering the corresponding C3 trifluoroalkyl quinoxalin-2(1 H )-one ( 4aa ) selectively (Table 1, entries 1–5). Possibly due to the competitive BET surface area, 19 2D-COF-5 (constructed using [2,2′-bipyridine]-5,5′-dicarbaldehyde and 4,4′,4′′,4′′′-(1,9-dihydropyrene-1,3,6,8-tetrayl)tetraaniline) substantially enhanced the reaction efficiency. Further screening disclosed that 2D-COF-5 was indispensable for a high substrate conversion (entry 6), and the wavelength of visible light should be 456 nm for the best output of the desired product 4aa (Table S1, see details in the ESI†).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Then, they were used as heterogeneous photocatalysts in sequence for the visible-light-induced three-component reaction of quinoxalin-2(1 H )-one ( 1a ), phenyl propylene ( 2a ), and CF 3 SO 2 Na under the blue LED irradiation in dioxane at room temperature for 24 h. We observed that most of them were effective for the reaction, delivering the corresponding C3 trifluoroalkyl quinoxalin-2(1 H )-one ( 4aa ) selectively (Table 1, entries 1–5). Possibly due to the competitive BET surface area, 19 2D-COF-5 (constructed using [2,2′-bipyridine]-5,5′-dicarbaldehyde and 4,4′,4′′,4′′′-(1,9-dihydropyrene-1,3,6,8-tetrayl)tetraaniline) substantially enhanced the reaction efficiency. Further screening disclosed that 2D-COF-5 was indispensable for a high substrate conversion (entry 6), and the wavelength of visible light should be 456 nm for the best output of the desired product 4aa (Table S1, see details in the ESI†).…”
Section: Resultsmentioning
confidence: 99%
“…, oxidation, 13 reduction, 14 cyclization, 15 C–H functionalization, 16 E – Z isomerization, 17 cross-coupling, 18 and cascade C–H bond activation/cyclization. 19 Notably, the diversity of organic building blocks endows 2D-COFs with an unlimited tunability of their photocatalytic performance, providing massive potential to expand their applications to more sophisticated photocatalytic organic processes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…transcribed to other synthetically relevant transformations. In certain cases, some ligand-free inorganic metal salts [51][52][53][54][55][56][57][58] and metal-embedded organic frameworks [59][60][61][62][63][64][65][66][67] could achieve cross-couplings in the absence of external PCs, 68 although these systems remain underdeveloped and mostly limited to C-X bond formation.…”
Section: The Bigger Picturementioning
confidence: 99%